2000
DOI: 10.1038/sj.bmt.1702543
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of ex vivo differentiated myeloid precursors after high-dose chemotherapy and peripheral blood progenitor cell rescue

Abstract: Summary:The infusion of ex vivo differentiated myeloid precursors may be able to shorten the period of obligatory neutropenia after high-dose chemotherapy and peripheral blood progenitor cell rescue by providing cells capable of differentiating to mature neutrophils within days of infusion. To test this hypothesis, 21 female patients with metastatic breast cancer underwent progenitor cell mobilization with cyclophosphamide, etoposide and G-CSF. CD34+ cells from one to two leukapheresis products were isolated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Besides, CD66b + UCB neutrophils are presented in the peripheral blood of recipient mice much longer than peripheral blood neutrophils, strongly suggesting that the ex vivo generated neutrophils (and progenitors) can further mature in vivo . To date, a few research groups have investigated ex vivo expansion of neutrophil progenitors from HSCs [5860], and in two such studies, expanded cells have been used clinically for providing autologous HSCs. In the current study, we have injected cryopreserved neutrophil progenitor cells (day 9 culture) into neutropenia NOD/SCID mice via the tail vein.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, CD66b + UCB neutrophils are presented in the peripheral blood of recipient mice much longer than peripheral blood neutrophils, strongly suggesting that the ex vivo generated neutrophils (and progenitors) can further mature in vivo . To date, a few research groups have investigated ex vivo expansion of neutrophil progenitors from HSCs [5860], and in two such studies, expanded cells have been used clinically for providing autologous HSCs. In the current study, we have injected cryopreserved neutrophil progenitor cells (day 9 culture) into neutropenia NOD/SCID mice via the tail vein.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have attempted to examine the impact of ex vivo expansion on haematopoietic recovery. These studies have utilized various combinations of cytokines, used different methods of cell expansion and investigated patients with various disease types (Reiffers et al , 1999; Williams et al , 1996; McNiece et al , 2000; Paquette et al , 2000; Zimmerman et al , 2000; Engelhardt et al , 2001; Devine et al , 2003; Reichle et al , 2003). The studies by Reiffers et al (1999), Paquette et al (2000) and McNiece et al (2000), all utilized the same cytokine combination as in our study and they too demonstrated an impact on neutrophil recovery; however interpretation of the data is hampered because their comparators were historical controls.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, preclinical data indicates that both myeloid and megakaryocytic progenitors can be expanded in static culture systems with various growth factor combinations (Haylock et al , 1992; To et al , 1997). To date, several clinical ex vivo expansion studies based on this rationale have been performed, using a variety of culture systems and cytokine combinations (Reiffers et al , 1999; Williams et al , 1996; McNiece et al , 2000; Paquette et al , 2000; Zimmerman et al , 2000; Engelhardt et al , 2001; Reichle et al , 2003). Although a number of these studies have demonstrated a positive impact on myeloid cell recovery (with one demonstrating a modest impact on platelet recovery; Paquette et al , 2000) all except one study (Reichle et al , 2003) have utilized historical control patients.…”
mentioning
confidence: 99%
“…There was a significant correlation between the time to neutrophil recovery and the total expanded nucleated cells/kg, but not the CD34+ cell dose/kg. Zimmerman and colleagues expanded CD34+ selected PBPC in the presence of PIXY321 in 21 women with metastatic breast cancer, infusing the expanded product as a supplement to the unselected PBPC autograft [9]. They observed no toxicity associated with the EVE-PBPC infusion and noted a significant inverse relationship between the dose of differentiated myeloid precursors and the depth and duration of neutropenia.…”
Section: Selected Cd34+ Cellsmentioning
confidence: 99%
“…An increasing number of clinical trials investigating the administration of EVE PBPC following high-dose chemotherapy are being reported, and to date, intravenous administration of EVE hematopoietic progenitors, cultured in the presence of a wide variety of cytokine combinations, has not been associated with toxicity [3][4][5][6][7][8][9][10]. Hematopoietic progenitors may be expanded ex vivo, while retaining their capacity to reconstitute hematopoiesis [7].…”
Section: Previous Human Experiencementioning
confidence: 99%